The Relationship Between Academic Stress and Sleep Quality Among Nursing Students - Nurwahida Yulianti; Nur Melliza (Pubfine Media Group, 2025)
Introduction: Academic stress is a common psychological condition among nursing students, often resulting from heavy academic workloads, time pressure, and high performance expectations. Prolonged academic stress may negatively affect students’ physical and mental health, particularly their sleep quality, which plays a vital role in cognitive performance, emotional regulation, and overall well-being. This study aimed to determine the relationship between academic stress and sleep quality among Nursing Science students. Methods: This research employed an analytical observational design using a cross-sectional approach. The population consisted of undergraduate Nursing Science students, with samples obtained through stratified random sampling. Data were collected using standardized questionnaires measuring academic stress levels and sleep quality. The data were analyzed using the Spearman rank correlation test to identify the relationship between variables. Results: The findings revealed that most respondents experienced moderate to high levels of academic stress and poor sleep quality. Statistical analysis showed a significant correlation between academic stress and sleep quality (p < 0.05), indicating that students with higher academic stress levels were more likely to experience poor sleep quality. Conclusion: There is a significant relationship between academic stress and sleep quality among nursing students. Increased academic stress contributes to disrupted sleep patterns through both physiological and psychological mechanisms. Universities are encouraged to implement stress management programs, promote time management training, and provide mental health support services to enhance students’ well-being and academic performance.